Synthesis and Characterization of Substituted 1,2,4-Triazole and Its Derivatives - JADHAV, SHIVAJI; RAI, MEGHA; KHILLARE, LALIT; DURRANI, AYESHA (Asian Journal of Chemistry, 2010)
Isoniazid was agitated with potassium hydroxide and carbon disulphide to yield sulphur-potassium salt which on refluxed with hydrazine hydrate/ammonia to give substituted 1,2,4-triazoles. The synthesized compounds have been characterized by spectral and elemental analysis.